Four‐G Episode and the elevated risks. (November 2016) - Azis, Iwan J
Abstract : Complacency and a false perception that markets will correct imbalances during two decades of 'Great Moderation' led to 'Global Imbalances'. The low interest rates and a lack of proper oversight, combined with a perception that housing prices will always move north, brought the sub‐prime crisis in the USA and the subsequent 'Global Financial Crisis' and European crisis. The Quantitative Easing policy in advanced economies (AE) created an even more permissive global liquidity. The externality affecting emerging markets (EM) took the form of massive capital inflows, first channelled through banks where the global banks‐mostly headquartered in Europe‐played a significant role and then through capital market with fund managers being the protagonist. The augmented liquidity spurred growth in EM but also elevated the risk of financial instability. Capital flows reversal, slower growth and less benign external conditions have put EM in a quandary. The uncertainty is heightened by a non‐synchronised monetary policy in AE ('Great Divergence'). To the extent that standard policies have become ineffective, and to defend from externality caused by AE's unilateral policy (financial nationalism), it is argued that EM can put a damper on the dangerous component of capital inflows. As part of macroprudential policy, such a measure is equivalent with discouraging risky behaviour to prevent financial instability and worsening income inequality.